Bacterial synthesis of phtocatalytically active and biocompatible TiO2 and ZnO nanoparticles - Singh, Sanjay; Britto, Virginia D.; Bharde, Atul A.; Sastry, Murali; Dhawan, Alok; Bhagavatula L. V. Prasad (International Journal of Green Nanotechnology: Physics and Chemistry, 2010)
TiO2 and ZnO nanoparticles are well known for their photocatalytic and ultraviolet (UV)-absorbent properties and have successfully entered into the market as consumer products. Large volume production of these nanoparticles by industries require environmentally friendly processes of synthesis. In this article, we show that when challenged with an appropriate precursor, the bacterium Actinobacter spp. can lead to the extracellular synthesis of ZnO and TiO2 nanoparticles. The biological way of synthesizing these materials probably leads to the in situ doping of elements like C, F, and N into their crystal lattices, which is evidenced by a red shift in the absorption edge. Because the doping is expected to affect the photocatalytic activity of these materials under different light conditions, such investigations have also been undertaken here. Further, the biocompatibility of these nanomaterials (cytotoxicity and genotoxicity) has also been investigated in detail.
Keywords: Biosynthesis; genotoxicity; Nanoparticles; Nanotoxicity; Photocatalysis